Mapping Trends and Hotspots Regarding the Use of Ultrasound in Emergency Medicine: A Bibliometric Analysis of Global Research - Wang, Sheng; Xia, Demeng; Zhang, Zhentao; Zhang, Jingli; Meng, Wenhao; Zhang, Yanping; Xu, Shuogui (Frontiers in Public Health, 2021)
Objective: Diagnostic tools in emergency medicine have been widely studied. As a non-invasive and quick tool, ultrasound plays a role in the field of emergency medicine. Thus, it is significant to understand the global scientific output of this topic. An analysis of publications on the use of ultrasound in emergency medicine over the past decade was performed and summarized to track the current hotspots and highlight future directions. Methods: Globally relevant publications on ultrasound in emergency medicine from 2009 to 2020 were extracted from the Web of Science collection database. VOSviewer software and CiteSpace were employed to visualize and predict the trends in the research on the topic. Results: The overall volume of global publications is on the rise; furthermore, the United States published the most publications in this field and had the most citations and H-index. University of California at San Francisco in the United States has most publications in terms of institutions. The American Journal of Emergency Medicine published the most papers related to ultrasound in emergency medicine in terms of journals. Pulmonary embolism was once the main research direction, and importantly, “point-of-care ultrasound” was determined to be a new research hotspot. Conclusion: Altogether, the number of publications on ultrasound in emergency medicine will rise in the future. In addition, the findings reported here shed new light on the major progress on ultrasound in emergency medicine, which may be mutually cooperative in various fields. Moreover, this bibliometric study provides further indications for the topic of “point-of-care ultrasound”.